IMPLEMENTATION OF ONE DOOR INTEGRATED SERVICES (PTSP) IN IMPROVING PUBLIC SERVICES AT THE MINISTRY OF RELIGION OFFICES BARRU DISTRICT - AZ, Wahyul; Asriani; Mariyati (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal